Riociguat for the treatment of transthyretin cardiac amyloidosis: data from a named patient use program in Austria. (November 2019) - Duca, Franz; Aschauer, Stefan; Zotter-Tufaro, Caroline; Binder, Christina; Kammerlander, Andreas A.; Börries, Benedikt; Agis, Hermine; Kain, Renate; Hengstenberg, Christian; Mascherbauer, Julia; Bonderman, Diana
Patients with transthyretin cardiac amyloidosis (TTR CA) suffer from impaired exercise capacity, have a poor quality of life (QoL), and approved treatments are lacking. Stimulators of the soluble guanylate cyclase are promising new pharmaceuticals in the treatment armamentarium of heart failure patients. The aim of the present study was to report on the safety and efficacy of riociguat administration in patients with TTR CA. TTR CA patients received riociguat for 4–6 months within the frames of a national named patient use (NPU) program. Parameters of interest included changes in submaximal exercise capacity, invasive hemodynamic parameters, and QoL. Between March 2012 and June 2017, 86 CA patients were screened for the NPU program, of whom 13 TTR CA patients were eligible for participation. In our study cohort, riociguat had an acceptable tolerability profile. At follow-up, we could detect slight improvements in median 6-min walk distance (396 m [interquartile range (IQR) = 340–518] vs. 400 m [IQR = 350–570], P = 0.045), New York Heart Association class ≥ III (n = 7 [53.9%] vs. n = 0 [0.0%], P = 0.031), cardiac output (4.3 L/min [IQR = 3.9–5.1] vs. 4.5 L/min [IQR = 4.2–5.1], P = 0.022), diastolic pressure gradient (1.0 mmHg [IQR = −1.5–3.0) vs. −1.0 mmHg [IQR = −3.0–1.0], P = 0.049), and QoL (50.0% [IQR = 40.0–58.0] vs. 60.0% [IQR = 50.0–75.0], P = 0.021). Pulmonary arterial pressures were not altered. The present case series of TTR CA patients indicates that riociguat administration was safe and associated with minor clinical as well as hemodynamic improvements.